Research priorities for back pain: Results from an adapted James Lind Alliance priority setting partnership - Rikke Munk Killingmo; Ingrid Fjeldheim Bånerud; Astrid Torgersen Lunestad; Anne Marie Selboskar Selven; Eli Steen; Ann Iren Eikrem; Inger Ljøstad; Thale Skogstad; Kjersti Storheim; Amy Martinsen (PLoS ONE, 2026)
Background Knowledge gaps remain in the field of back pain research, with few systematic efforts undertaken to identify research priorities that reflect the preferences of individuals affected by the condition. The objective of this study was to identify the top 10 research priorities for back pain, as defined by individuals with lived experience of back pain and healthcare professionals. Method A James Lind Alliance Priority Setting Partnership approach was conducted in Norway. This involved (1) establishing a Steering Committee; (2) defining a scope; (3) gathering stakeholders’ evidence uncertainties about back pain using focus group interviews; (4) summarising evidence uncertainties and verifying uncertainties by checking existing evidence; (5) shortlisting evidence uncertainties using an online survey; and (6) determining the top 10 research priorities through a priority-setting workshop. Results In total, 230 questions were generated through three focus group interviews involving 12 individuals with lived experience of back pain and seven healthcare professionals. Generated questions were summarised into 37 core questions. None of the core questions had been sufficiently addressed by existing evidence (prioritising high-quality evidence, preferably systematic reviews). The shortlisting survey was completed by 284 respondents (263 individuals with lived experience of back pain (93%), and 40 healthcare professionals (14%), with some respondents identifying as both). The top 25 core questions were brought forward to the priority-setting workshop involving five healthcare professionals and four individuals with lived experience of back pain. The top research priority was “How can implementation of evidence-based treatment recommendations for back pain be ensured in the Norwegian healthcare system?”. Conclusion Adopting the JLA approach, this study has identified the top 10 research priorities for back pain from the perspectives of both individuals with lived experience of back pain and healthcare professionals. These findings should be considered a guide to research areas that are meaningful to end-users.